Switching costs, customer satisfaction, and their impact on marketing ethics of medical schemes in South Africa: An enlightened marketing perspective - Thabang Excellent Mofokeng (Cogent Business & Management, 2020)
The issue regarding the transition of members from their current medical schemes to the National Health Insurance (NHI) in South Africa has erupted in much debate. This study, modelled on enlightened marketing philosophy concepts, measures the effects of the perceived costs classified by type (procedural, financial, and relational) and direction (positive and negative) of this switch in terms of Customer Satisfaction. It also measures the impact on the perceived marketing ethics of current medical schemes in South Africa. Data were collected using a face-to-face survey from 250 consumers of medical schemes in South Africa. An 83.2% response rate was entered into SPSS Version 26, and AMOS Version 26 to test a two-step modelling approach (SEM). The results reveal positive significant effects of personal relational loss costs and benefit loss costs on Customer Satisfaction, which in turn, negatively affects currently perceived marketing ethics of medical schemes. For customers paying high and medium medical scheme contributions, and those who have prior switching experience, the results show that the costs of increasing benefit loss enhance Customer Satisfaction. Increasing satisfaction then enhances perceptions of marketing ethics for customers who do not have switching experience. The practical implications and recommendations explain marketing strategies to medical scheme practitioners to enable the enhancement of personal relationships with customers and increase the service benefits, which in turn, removes the current negatively perceived marketing ethics. This paper, therefore, links articulation of the disconfirmation Expectation Theory and the General Theory of Marketing Ethics in the context of medical schemes in South Africa. Limitations and relevant future research avenues conclude the discussion of the research study.
Keywords: 650; switching costs; customer satisfaction; marketing ethics; medical schemes; NHI; South Africa